MANAJEMEN KESISWAAN DALAM MENINGKATKAN BUDAYA KARAKTER RELIGIUS DI MADRASAH IBTIDAIYAH KABUPATEN OKU TIMUR - Anis Azmiatu Silvia; Septuri; Ahmad Fauzan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The culture of religious character is manifested in building a neat and structured culture at various levels of education. It is highly appropriate to implement this with the foundation of religious character values within students, as it will strengthen their faith and the application of these Islamic values can be nurtured through the school environment. Building a religious culture is very important and will indirectly influence the nature, attitudes, and actions of students. The goal of religious character education is the realization of awareness in applying normative values, which has a significant influence. Broadly speaking, this research aims to understand student management in enhancing the culture of religious character at Madrasah Ibtidaiyah in Oku Timur Regency. This research uses a qualitative approach with research locations at MIN 2 Oku Timur and MIS NU Sumedangsari Oku Timur. Data collection was carried out using observation, interviews, and documentation techniques. The validity of the data was ensured through source triangulation. The research results show that through structured student management, MIN 2 and MIS NU Oku Timur not only create a conducive academic environment but also instill strong religious values in students. With well-planned and closely monitored programs, these two madrasahs have successfully shaped students who are disciplined, responsible, and have a high love for Islamic teachings, making them individuals of noble character who are ready to contribute to society.